Pelatihan dan Pendampingan Aparat Desa untuk Persiapan Desa Mandiri Informasi - Mohamad Syafri Tuloli; Arip Mulyanto; Dian Novian (Univeristas Negeri Gorontalo, 2022)
The achievement of SDGs at the village level always involves information management to optimize planning, implementation, coordination, and evaluation of development programs. Information management requires knowledge and skill to sue the information technology services that are now widely available, unfortunately, village governments often have limitations in human resources capabilities, so they must depend on other elements (government, academics, volunteers) to utilize information technology. This does not supposed to happen, because many information technology services are designed to be used with no technical skill to operate. In this community service, we give training and assistance about introduction and empowerment of village officials to the use of information technology services that are easy to use, so that they can produce villages that are independent in managing information, to support the development. The training and mentoring succeeded in making participants understand about internet services, and have the willingness to apply them in their work environment in the village.